Education, Gender, and Cohort Fertility in the Nordic Countries - Jalovaara Marika; Neyer Gerda; Andersson Gunnar; Dahlberg Johan; Dommermuth Lars; Fallesen Peter; Lappegård Trude (Stockholm University, 2022)
Abstract: Systematic comparisons of fertility developments based on education, gender and country context are rare. Using harmonized register data, we compare cohort total fertility (CTF) and ultimate childlessness by gender and educational attainment for cohorts born beginning in 1940 in four Nordic countries. CTF has remained fairly stable in all countries. Childlessness, which had been increasing, has plateaued except in Finland. Women’s negative educational gradient has vanished, while men’s positive gradient has persisted. The highest level of men’s childlessness appears among the less educated, revealing striking educational differences. Childlessness has increased among low-educated women but not among highly educated women. The educational gradient in women’s childlessness has shifted from positive to negative. Thus, we witness both a new gender similarity and widening social inequalities in childbearing in the Nordic welfare states. Low-educated citizens of both sexes have apparently become an increasingly marginalized segment with regard to childbearing.